Ultimate Performance Analysis Tool (uPATO) - Silva, F. G. M.; Nguyen, Q. T.; Correia, A. F. P. P.; Clemente, F. M.; Lourenço Martins, F. M. (Springer Briefs in Applied Sciences and Technology, 2019)
This book introduces the ultimate performance analysis tool (uPATO) as a new software to compute social network metrics in the scope of team sports analysis. The reader will identify the algorithms to test the general properties of the team, the co-dependencies and the centrality levels of players, i.e. to evaluate the individual, sub-group, and team performance analysis. As uPATO tool implements the metrics for all options, namely for unweighted graphs, weighted graphs, unweighted digraphs and weighted digraphs, it is also useful for network analysis into other areas beyond team sports. The book assists the reader to compute the metrics and to use it in different scenarios.